2021
DOI: 10.1253/circj.cj-21-0819
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Reversal of Frailty in Heart Failure ― A Systematic Review ―

Abstract: Background: Frailty is prevalent in patients with heart failure (HF) and associated with increased morbidity and mortality. Hence, there has been increased interest in the reversibility of frailty following treatment with medication or surgery. This systematic review aimed to assess the reversibility of frailty in patients with HF before and after surgical interventions aimed at treating the underlying cause of HF. It also aimed to assess the efficacy of cardiac rehabilitation and prehabilitation in reversing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…Because 80% of all patients were over 80 years of age, we believe that this was to prevent frailly. 25 , 26 “Salt intake” and “smoking cessation” as lifestyle guidance for patients with HF were also frequently selected. However, the selection of “explanation of the need to visit a medical institution” and “guidance on the prevention of infectious diseases” was significantly lower in accepting facilities (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Because 80% of all patients were over 80 years of age, we believe that this was to prevent frailly. 25 , 26 “Salt intake” and “smoking cessation” as lifestyle guidance for patients with HF were also frequently selected. However, the selection of “explanation of the need to visit a medical institution” and “guidance on the prevention of infectious diseases” was significantly lower in accepting facilities (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The PEARL study demonstrated improvements in a physical performance battery after cardiac rehab; despite reporting no adverse outcomes, improvement in death and hospitalization was not measured. 109 Other trials have demonstrated a reversal of some frailty in heart failure patients, 110,111 which may translate into reducing poor outcomes indirectly. Others have shown improvement in mental health after these programs.…”
Section: Preoperative Anemiamentioning
confidence: 99%
“…As has been learnt from the TEER experience, 6 symptoms of heart failure and frailty are commonplace in TMVR cohorts, and careful optimization of guideline‐directed medical therapy should be prioritized for all patients before intervention 21,22 . This includes electrophysiology assessment and/or cardiac resynchronization device therapy where appropriate, correction of iron deficiency anaemia and physical conditioning, termed prehabilitation 23 .…”
Section: Prevention and Reversal Of Heart Failure And Frailtymentioning
confidence: 99%
“…This includes electrophysiology assessment and/or cardiac resynchronization device therapy where appropriate, correction of iron deficiency anaemia and physical conditioning, termed prehabilitation 23 . Two studies have reported on the benefits of cardiac prehabilitation prior to surgery, although none prior to TMVR 22,24,25 . A home‐based exercise programme whilst awaiting TMVR should be considered within the limitations of the patient's pre‐operative functional class 24 …”
Section: Prevention and Reversal Of Heart Failure And Frailtymentioning
confidence: 99%